Perancangan Mesin Centrifugal Untuk Optimalisasi Tenaga Sortir Sampah Plastik - Darsini; Yustinus Nandha Dian; Suprapto (Indonesian Society of Applied Science, 2021)
PT. XXX as the yield management company becomes a plastic seed product that is ready to be used as raw material in other plastic companies. Apart from the garbage production of PT. Garuda Prima Sentosa also gets unused plastic waste from domestic and foreign suppliers. In the process of processing plastic waste, still uses the sorting power manually obtained by 40 people, the results obtained are also less than the maximum there are still many other materials mixed in plastic waste from 4200 kg of plastic waste can only be repaired by other unused material as much as 915.92 kg per day. This study discusses the centrifugal machine as a separator between used plastic waste from other unused materials and minimizes the sorting power of 40 people to 8 people, and adds the unused material to 1355,308 kg per day. The design of this Centrifugal machine to be able to overcome the problems that exist in the sorting section so that it can produce cleaner plastic seeds and improve the sorting process.